Systematic assessment of triticale‐based biorefinery strategies: a biomass procurement strategy for economic success. (2nd June 2015) - Melendez, Jose; Stuart, Paul R
Abstract: An economical supply of biomass feedstock is an essential part of any biorefinery project. With procurement costs accounting for nearly 50% of operating costs, current biomass supply chain and procurement operations must be continuously improved to reduce procurement costs. Strategic negotiations between the farmer (the producer) and the end user (the biorefinery), in which both parties benefit, should also take place. This study examines procurement supply chains for triticale, for a biorefinery, and proposes a financial model that will satisfy both producer and end user. A biomass cost model was developed to determine the procurement costs of triticale biomass. Several biomass procurement supply chain alternatives were evaluated. Results from the study determined that a biorefinery would pay 225 per tonne of biomass for the delivery of 250 002 tonnes of triticale grain and 265 791 tonnes of triticale straw per year. In addition, the study shows that increased yields of triticale and its similarities in growing and harvesting methods with currently produced agricultural crops will rapidly enable it to become a viable feedstock source for biorefineries. The biomass procurement strategy described appears to be an attractive alternative for producers and provides a good basis for furnishing a long‐term cost‐competitive supply of feedstock to the triticale biorefinery. This financial model is based on the premise that the risk and cost of developing increasingly engineered triticale crops will be borne by the biorefinery owner. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd